Impact of In-Row Planting Patterns on Reniform Nematodes Using Precision Agriculture in Cotton: SS-AGR-55/AG183, rev. 9/2022 - Wright, David L.; George, Sheeja; Small, Ian; Stansly, Theodor; Grabau, Zane (EDIS, 2022)
This article is intended to inform cotton producers and associated agricultural professionals of a practical method to help manage plant-parasitic nematodes in cotton. Written by D. L. Wright, S. George, I. Small, T. Stansly, and Z. Grabau, and published by the UF/IFAS Agronomy Department, revised September 2022. SS-AGR-55/AG183: Impact of In-Row Planting Patterns on Reniform Nematodes Using Precision Agriculture in Cotton (ufl.edu)